Significance of Human Papilloma Virus genotyping in cervical cancer screening - Sharma, Poonam; Sharma, Sarabjeet; Mrs Arti (Tropical Journal of Pathology and Microbiology)
Background and Objectives: Detection of specific human papillomavirus (HPV) genotypes may be useful for identifying those women who are at lower and higher risk for cervical precancer and cancer .Cervical cancer is the most common cancer and leading cause of cancer deaths in women in developing countries. Therefore, the present study was undertaken with the aim of identifying the most frequent HPV genotypes associated with different cervical lesions. Materials and Methods: The study was a retrospective cross-sectional study conducted over a period of one and a half years i.e. from January2015 to July 2016, on women attending obstetrics and gynaecology department of a tertiary care hospital. One hundred eighty three consecutive scrape samples or cervical brushings were collected from women presenting with any type of cervical lesions. DNA was extracted from the clinical sample using Hybribio DNA extraction kit. Hybribio HPV genoarray test kit was used to genotype the HPV risk groups. Results: Out of 183 cervical brushings collected over a period of one and a half years, 22 (12%) were positive for HPV genotypes. Among the latter, HPV18 genotype was observed in 12(54.5%), HPV16 genotype in 3 (13.6%) and HPV53 genotype in 2(9.09%). One of the genotypes 68, 52, 39, 33 and 56 were present in rest of the samples. Conclusion: Most common genotypes associated with cervical lesions in the present study were genotype 18 followed by 16 which shows that cervical cancer screening should rely on measuring the causal viral infection, oncogenic HPV, rather than the pleomorphic cellular changes caused by the infection.